2011
DOI: 10.1038/nature09923
|View full text |Cite
|
Sign up to set email alerts
|

Evolved structure of language shows lineage-specific trends in word-order universals

Abstract: Languages vary widely but not without limit. The central goal of linguistics is to describe the diversity of human languages and explain the constraints on that diversity. Generative linguists following Chomsky have claimed that linguistic diversity must be constrained by innate parameters that are set as a child learns a language 1,2 . In contrast, other linguists following Greenberg have claimed that there are statistical tendencies for co-occurrence of traits reflecting universal systems biases [3][4][5] , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
355
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(368 citation statements)
references
References 25 publications
10
355
1
2
Order By: Relevance
“…However, we do not find any correlation between the structural linguistic distances and the geographical distances predicted by any model of migration. This probably reflects the paucity of structural data available for the Bantu languages together with the absence of variation in such data [38]. Therefore, more informative structural data, comparable with those collected by Reesink et al [39], would be needed to investigate the complex expansion history of the Bantu languages.…”
Section: Discussion (A) Demic Diffusion Of Bantu-speaking Peoplesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not find any correlation between the structural linguistic distances and the geographical distances predicted by any model of migration. This probably reflects the paucity of structural data available for the Bantu languages together with the absence of variation in such data [38]. Therefore, more informative structural data, comparable with those collected by Reesink et al [39], would be needed to investigate the complex expansion history of the Bantu languages.…”
Section: Discussion (A) Demic Diffusion Of Bantu-speaking Peoplesmentioning
confidence: 99%
“…summary in [37]) [38], we applied our method to eight structural features reported for 66 Bantu languages [38]. However, we do not find any correlation between the structural linguistic distances and the geographical distances predicted by any model of migration.…”
Section: Discussion (A) Demic Diffusion Of Bantu-speaking Peoplesmentioning
confidence: 99%
“…Phylogenetic methods have revolutionized the biological sciences and have recently been used to make inferences about cultural evolution ranging from the kinship system of Proto-Indo-European and Austronesian cultures [14], to the evolution of political complexity across Austronesia [15], and the determinants of language structure [16]. Here we use a phylogenetic method to first test whether beliefs in MHGs and BSP coevolve with political complexity.…”
Section: Introductionmentioning
confidence: 99%
“…But correlations between features are observed that go beyond those normally discussed in typology, or those observed by Dunn et al (2011). Interestingly, there are also some modest cross-correlations between grammatical features and phonemes.…”
Section: Some Preliminary Resultsmentioning
confidence: 75%
“…Biases can be seen either in the synchronic patterns of language features today, or in the diachronic patterns of transition probabilities between features as languages culturally evolve (e.g. Dunn et al, 2011). Patterns that reveal biases may be found in any aspect of language, e.g.…”
Section: Introductionmentioning
confidence: 99%